Neuregulin, an Effector on Mitochondria Metabolism That Preserves Insulin Sensitivity - Gumà, Anna; Díaz-Sáez, Francisco; Camps, Marta; Zorzano, Antonio (Frontiers in Physiology, 2020)
Different external factors modulate metabolic efficiency of mitochondria. This review focuses on the impact of the growth factor neuregulin and its ErbB receptors on mitochondria and their relationship with several physiopathological alterations. Neuregulin is involved in the differentiation of heart, skeletal muscle and neuronal system, among others, and its deficiency is deleterious for the individual. Information gathered over the last two decades suggests that neuregulin plays a key role regulating mitochondrial oxidative machinery, which sustain cell survival and insulin sensitivity.